(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This qualitative study was embarked with the aim of exploring school leaders’ practices in enhancing unity among Malaysian secondary school leaders. The instrument used for collecting data involved visiting the participated schools in order to conduct individual face-to-face interviews involving 12 participants who are secondary school leaders (principals and senior assistants). The data were analyzed manually. The findings showed that school leaders have not yet fully played their role to instill the 10 values of unity as proposed in the Model of Unity. The policy on unity emphasized by school leaders is only the usage of Malay Language. However, findings showed that in order to enhance unity, school leaders will remind teachers and students about unity in school gathering and meeting. School leaders will also remind multi-racial teachers and students to celebrate all the festivals, to participate in school activities, to respect each other in terms of cultural and religious differences, to instill unity values during school activities, to avoid sensitive issues and to be fair to all races. The managerial implication is school leaders need to do more practices to enhance unity. Therefore, they need more training to understand better the 10 values of unity, and to get knowledge and skills to inculcate values effectively. The findings of this study could benefit readers on the activities that they could employ to enhance unity in their institution.